Vibrational behavior of cross-laminated timber-concrete composite beams using notched connectors. (15th December 2021) - Thai, Minh-Van; Elachachi, Sidi Mohammed; Ménard, Sylvain; Galimard, Philippe
Highlights: Static and dynamic experimental tests were performed on cross-laminated timber (CLT)-concrete composite beams using notched connectors. Stiffness of notched cross-section of CLT was calibrated. Simplified finite element models were developed and validated. Experimental results were compared with recent experimental studies in the literature. Abstract: The CLT-concrete composite (CCC) solution is appealing since it possesses many advantages of a timber-concrete composite flooring system with a small thickness. However, the vibration criteria is usually an obstacle in the design process, especially more onerous for the long-span floor. The present study focus on the dynamic properties (fundamental frequency and damping) of CCC beams featured notched connectors. Three composite beams were fabricated and tested. The experimental natural frequencies were compared with analytical and numerical results. Some improvement in terms of the fundamental frequency and modal damping was found in the CCC beams compared to bare CLT beams. A significant gap between the experimental and theoretical fundamental frequency was observed in the case of a non-composite beam. Modal damping was negatively correlated to the number of notches of the beams. Finally, the analysis was expanded to other literature studies to validate our experimental and numerical results.